2015
DOI: 10.1364/ol.40.001018
|View full text |Cite
|
Sign up to set email alerts
|

Incident-polarization-sensitive and large in-plane-photonic-spin-splitting at the Brewster angle

Abstract: In this Letter, we report a phenomenon of large in-plane-photonic-spin-splitting (IPPSS) in the case of a linear polarized Gaussian light beam reflected from an air-glass interface at the Brewster angle. The IPPSS-induced displacement reaches ∼12.4  μm, which is quite larger than the previously reported value. Particularly, the IPPSS is extremely sensitive (∼70  μm/deg) to the incident polarization. We also find that the direction of the spin accumulation can be switched by adjusting the incident polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…For a two-dimensional (2D) Gaussian beam, however, the OPSS could only reach 0.4 w 0 . It was demonstrated recently that the IPSS could also be enhanced near Brewster incidence 17 . The IPSS shows advantage over the OPSS since it can be tuned flexibly by the incident polarization state.…”
Section: Introductionmentioning
confidence: 99%
“…For a two-dimensional (2D) Gaussian beam, however, the OPSS could only reach 0.4 w 0 . It was demonstrated recently that the IPSS could also be enhanced near Brewster incidence 17 . The IPSS shows advantage over the OPSS since it can be tuned flexibly by the incident polarization state.…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal spatial shift under conditions of partial reflection was investigated experimentally for the Brewster angle of incidence [29]. It turned out that the longitudinal shift is exceptionally sensitive to a change in the azimuth of linear polarization in the vicinity of 0    .…”
Section: Spatial and Angular Shifts Incident To Refraction And Reflecmentioning
confidence: 99%
“…However, most of these techniques just deal with SHEL around the Brewster angle for horizontally or vertically polarized incident beam. Most recently, Qiu et al reported a large in-plane spin-dependent splitting at Brewster angle and demonstrated that the spin-dependent splitting direction can be switched by slightly adjusting the polarization orientation of the incident beam [19].…”
Section: Introductionmentioning
confidence: 99%
“…In considerable amount of measurements, the pre-and postselection processes are implemented by using two nearly crossed Glan-Taylor polarizers (GTPs) [5][6][7][9][10][11][12], of which we can choose the optimal pre-and post-selection to acquire the maximum weak value [17]. Nevertheless, Kong et al present an effective solution consisting of two polarizers with an angle of 45 • to measure the SHEL around the Brewster angle [18,19]. In the past few years, it has aroused considerable amount of investigations to manipulate the magnitude and direction of spin splitting [19][20][21][22][23][24] Abstract As Brewster law goes, the polarization selectivity when a light beam reflected at Brewster angle is feasible.…”
mentioning
confidence: 99%
See 1 more Smart Citation